The Urge to Tell It Backwards: The Contemporary Poet and the Great War. (November 2014) - Lowe, Peter
<x content-type="archive" xml:space="preserve">Abstract</x> At the start of the twenty-first century many poets are turning their focus again to the First World War as a subject, often 'revisiting' poems from the time and composing modern responses to them: an approach best seen in Carol Ann Duffy's edited collection 1914: Poetry Remembers (2013). In some cases the modern poet enacts this 'remembrance' by considering the poem as a space within which alternative versions of events may be explored: a work in which the past may be re-written, with history shown to be changeable. Using Duffy's poem 'Last Post' as a case study, and drawing upon recent scholarship on the challenges of 'narrating' war in textual terms, this essay argues, however, that such a tendency to wish the past 'undone' says more about our view of the Great War in the early twenty-first century than it arguably tells us about the poetry of the conflict itself. The poet of 2013 wishes the Great War undone not only out of a desire to avoid its losses but out of the realization that it did not provide the resolution or peaceful future that poets of the time hoped would emerge from its aftermath.